Compact and Real-Time Radiation Dosimeter Using Silicon Photomultipliers for In Vivo Dosimetry in Radiation Therapy - Jeongho Kim; Jeehoon Park; Byungdo Park; Yonghoon Kim; Beomjun Park; So Hyun Park (Sensors)
Existing dosimeters for radiation therapy are typically large, and their performance in in vivo system applications has not been assessed. This study develops a compact real-time dosimeter using silicon photomultipliers, plastic scintillators, and optical fibers and evaluates its in vivo applicability for radiation therapy. Dose calibration, dose-rate dependency and linearity, and short-term repeatability tests were conducted using solid water phantoms and bolus materials, and in vivo dosimetry was performed using an in-house phantom. The characterization evaluation results showed high linearity, with a coefficient of determination of 0.9995 for dose rates of 100–600 monitoring units (MU)/min, confirming an error rate within 2% when converted to dosage. In the short-term repeatability tests, the dosimeter exhibited good characteristics, with relative standard deviation (RSD) values lower than 2% for each beam delivery and an RSD value of 0.03% over ten beam deliveries. Dose measurements using the phantom indicated an average error rate of 3.83% compared to the values calculated using the treatment planning system. These results demonstrate a performance comparable to that of commercial metal-oxide-semiconductor field-effect transistors and plastic scintillator-based dosimeters. Based on these findings, the developed dosimeter has significant potential for in vivo radiation therapy applications.